(untitled) (Proceedings of International Educators Conference, 2024)
This article covers large-scale reforms aimed at creating favorable conditions for conducting business activities in the country’s tax spheres, and further strengthening the confidence of business circles. Reforms in the tax system play a decisive role in shaping the country’s economic landscape. In addition, Uzbekistan recognized the importance of reforming the tax system as a country with a growing economy and a desire to attract domestic and foreign investments. At the same time, some important reforms implemented in the tax system of Uzbekistan were studied, foreign experience, scientific-practical conclusions and suggestions on its application in our country were developed.